Risk Assessment and Spatiotemporal Variation of Microplastic Concentration, Size, and Polymer Type in Mayotte Lagoon’s Surface Water (Comoros Archipelagos) - Emilie Strady; Johnny Gaspéri; Damien Devault; Marc Pagano; Ngoc Nam Phuong; Sophie Ricordel; Clément Lelabousse; Mathieu Leborgne; Cristèle Chevalier (Microplastics)
The concentration of microplastics [300–5000 µm] in the surface water of the Mayotte lagoon, Western Indian Ocean, was measured over two snapshot campaigns conducted during the dry and rainy seasons. The concentration in the surface water varied from 0.01 MP m−3 to 1.23 MP m−3 and was higher during the rainy season. All particles were analyzed via µFTIR, enabling systematic polymer and surface area determination. Polypropylene dominated over polyethylene and polystyrene, representing 70% of the microplastic particles observed. The microplastics, which were predominantly in the [0.3–1000 µm] fraction, presented a similar seasonal trend of distribution with respect to their occurrence, suggesting that turbulence and the subsequent settling of microplastics in the lagoon’s surface water were identical during the two campaigns. PCA was performed to deconvolute the effects of season and hydrodynamic features on the observed surface water concentrations and median size distribution. It evidenced a high degree of disparity in concentration and median area in surface water during the rainy season, while a lower concentration of smaller particles was observed during the end of the dry season. A microplastic risk assessment was performed for the surface water of the lagoon and evidenced a low pollution load index and low to high polymer risk assessment and potential ecological risk indexes.